MoS2 nanosheet/MoS2 flake homostructures for efficient electrocatalytic hydrogen evolution. (1st May 2019) - Yang, Lei; Zhang, Jiajia; Feng, Chao; Xu, Guomei; Xie, Chenggen; Yuan, Xueqin; Xiang, Bin
Abstract: Recently, the Earth abundant material MoS2 has attracted considerable attention in electrocatalytic hydrogen evolution reaction (HER) due to its chemical stability and high electrocatalytic efficiency. However, the aggregation formed in nanosized MoS2 reduces the exposure of active edge sites which hampers its electrocatalytic HER activity. In this paper, we demonstrate a facile hydrothermal synthesis of MoS2 nanosheet/MoS2 flake (MSN/MSF) homostructures by using MoS2 flakes as templates. The feature and chemical composition of the homostructures were investigated by scanning electron microscopy, transmission electron microscopy, Raman characterization and x-ray diffraction. The unique structure of MSN/MSF homostructures provides abundant active edge sites in the edge and basal plane of MoS2 flakes, resulting in an enhanced electrocatalytic HER activity (the overpotential at the current density of 10 mA cm −2 is 260 mV, and the Tafel slope is 82 mV/decade). It is expected to become a potential substitute for expensive noble metals.